Sensorimotor learning with stereo auditory feedback for a brain-computer interface. - McCreadie, Karl A; Coyle, Damien H; Prasad, Girijesh (Medical & Biological Engineering & Computing, 2013)
Motor imagery can be used to modulate sensorimotor rhythms (SMR) enabling detection of voltage fluctuations on the surface of the scalp using electroencephalographic electrodes. Feedback is essential in learning to modulate SMR for non-muscular communication using a brain-computer interface (BCI). A BCI not reliant upon the visual modality not only releases the visual channel for other uses but also offers an attractive means of communication for the physically impaired who are also blind or vision impaired. This study demonstrates the feasibility of replacing the traditional visual feedback modality with stereo auditory feedback. Results from a pilot study were used to select the most appropriate sounds for auditory feedback based on three options: broadband noise and two anechoic instrument samples. Subsequently, an SMR BCI was used to examine the effect on sensorimotor learning with broadband noise utilising a modified stereophonic presentation method. Twenty participants split into equal groups took part in ten sessions. The visual group performed best initially but did not improve over time whilst the auditory group improved as the study progressed. The results demonstrate the feasibility of using stereophonic auditory feedback with broadband noise as opposed to other auditory feedback presentation methods and sounds which are less intuitive.